Physiological and molecular responses to variation of light intensity in rubber Tree (Hevea brasiliensis Muell. Arg.). - Li-feng Wang (Public Library of Science (PLoS), 2014)
Light is one of most important factors to plants because it is necessary for photosynthesis. In this study, physiological and gene expression analyses under different light intensities were performed in the seedlings of rubber tree (Hevea brasiliensis) clone GT1. When light intensity increased from 20 to 1000 µmol m(-2) s(-1), there was no effect on the maximal quantum yield of photosystem II (PSII) photochemistry (Fv/Fm), indicating that high light intensity did not damage the structure and function of PSII reaction center. However, the effective photochemical quantum yield of PSII (Y(II)), photochemical quenching coefficient (qP), electron transfer rate (ETR), and coefficient of photochemical fluorescence quenching assuming interconnected PSII antennae (qL) were increased significantly as the light intensity increased, reached a maximum at 200 µmol m(-2) s(-1), but decreased from 400 µmol m(-2) s(-1). These results suggested that the PSII photochemistry showed an optimum performance at 200 µmol m(-2) s(-1) light intensity. The chlorophyll content was increased along with the increase of light intensity when it was no more than 400 µmol m(-2) s(-1). Since increasing light intensity caused significant increase in H2O2 content and decreases in the per unit activity of antioxidant enzymes SOD and POD, but the malondialdehyde (MDA) content was preserved at a low level even under high light intensity of 1000 µmol m(-2) s(-1), suggesting that high light irradiation did not induce membrane lipid peroxidation in rubber tree. Moreover, expressions of antioxidant-related genes were significantly up-regulated with the increase of light intensity. They reached the maximum expression at 400 µmol m(-2) s(-1), but decreased at 1000 µmol m(-2) s(-1). In conclusion, rubber tree could endure strong light irradiation via a specific mechanism. Adaptation to high light intensity is a complex process by regulating antioxidant enzymes activities, chloroplast formation, and related genes expressions in rubber tree.